On (n,D)- quasi Operators - salim dawood mohsen (Iraqi Journal for Computer Science and Mathematics, 2024)
T Through the article, we will provide an entirely novel type of quasi operators base on the concept of D razin inverse in Operator theory which is named (n,D) -quasi operators on the Hilbert spaces, also we explain the sum, product, and other features of these classes are discussed. and restriction via some necessary conditions have been holds in order to obtain these operations, in addition that we investigate the scalar and power of this concept, moreover we submit prove of the Tensor product and direct product of (n,D)-quasi operators.